Fabrication, characterization and functionalization of single-walled carbon nanotube conjugated with tamoxifen and its anticancer potential against human breast cancer cells - Oskoueian, Arshin (2018)
Even though progress has been made in decreasing breast cancer mortality, it is still one of the major causes of death worldwide. Chemotherapy the most common cancer treatment has severe and lethal side effects. This thesis reports, the use of a drug delivery system for cancer treatment and single wall carbon nanotubes (SWCNT) employed as novel one-dimensional nanomaterials as a drug vehicle. The advantage of SWCNT is, they are capable of delivering therapeutic agents and imaging agents, having the ability to overcome various biological barriers and to localize into the target tissue. This approach not only resulted in enhanced efficacy of the drug but also minimized drug toxicity to the healthy tissues and organs. Due to the importance of cancer treatment and seeking for the safe alternative drug delivery vehicle this comprehensive study was started with the fabrication of SWCNT, its purification, characterization, functionalization followed by its toxicity evaluation (human hepatocyte) and anticancer potential determination against human breast cancer cells. In this study, the SWCNT was fabricated using modified chemical vapor deposition (CVD) method and the fabricated SWCNT subjected to the two-step acid purification technique. The results of Raman spectrometry, SEM, TEM, HRTEM microscopy and TGA confirmed the success of highly pure SWCNT synthesis. Moreover, the biocompatibility and toxicity of fabricated SWCNT to the human hepatocyte (Chang ATCC: CCL-13) was evaluated in vitro. The toxicity evaluation of SWCNT against human hepatocyte cells indicated that concentrations below 50 μg/ml of SWCNT appeared to be nontoxic to the human hepatocyte cells. With regard to the potential of SWCNT in the delivery of cancer drugs, it seems this concentration of SWCNT could be promising for the delivery of cancer drugs. In the next step, the SWCNT was functionalized to contain free carboxylic acid and hydroxyl groups to be loaded with tamoxifen (SWCNT-PEG). Then, the functionalized SWCNT (SWCNT-PEG) conjugated with tamoxifen (SWCNT-PEG-TAM) and further characterized using Fourier-transform infrared spectroscopy (FTIR) and nuclear magnetic resonance spectroscopy (NMR). The functionalization of SWCNT was performed by oxidizing of SWCNT, attachment of polyethylene glycol (PEG) to oxidized SWCNT, attachment of azelaic acid to the polyethylene glycol group. As result, the SWCNT with free functional carboxylic acid and hydroxyl groups (SWCNT-PEG) was developed. The SWCNT-PEG was then conjugated with tamoxifen (SWCNT-PEG-TAM). The FT-IR together with NMR results confirmed the conjugation of tamoxifen to functionalized SWCNT (SWCNT-PEG-TAM). Finally, the anticancer potential of SWCNT-PEG-TAM was determined against human breast cancer cells (MCF-7 ATCC: HTB22) as compared to the free tamoxifen. The cytotoxic concentrations (CC50, the concentration at which 50% of cells survive) of SWCNT-PEG, tamoxifen, and SWCNT-PEG-TAM were >100, 12.67±2.69, and 5.49±1.34 μg/ml, respectively. The linking of tamoxifen to functionalized SWCNT enhanced the cytotoxic action of tamoxifen against breast cancer cells up to 2.3 times. The results of the morphological examination and cytotoxicity assay confirmed the higher cytotoxic action of SWCNT-PEG-TAM as compare to free tamoxifen. Consequently, the results obtained in this study indicated that the delivery of tamoxifen through SWCNT-PEG-TAM enhanced the therapeutic effects and anticancer potential of tamoxifen against human breast cancer cells.